Dendrimers: A Novel Trend of Nanocarriers - Kavinila.S; Lavanya.B; Vigneshwaran.L; Senthil Kumar.M (Zien Journals, 2022)
Dendrimers are a brand-new type of polymer. They're monodisperse macromolecules with a lot of branches. Dendrimers' structural advantages enable them to play a significant role in nanotechnology, pharmaceuticals, and medicinal chemistry. Dendrimers are ideal for a wide range of biological and industrial applications due to their unique behavior. The bioactive substances can be easily encapsulated into the inside of the dendrimers or chemically conjugated or physically adsorbed onto the dendrimer surface, tailoring the carrier's desirable features to the active material's unique demands and therapeutic applications. The goal of the study is to highlight the production, characterization, drug delivery, and potential applications of dendrimers in diverse research, technological, and therapy fields.
Keywords: Drug delivery; Types; synthesis; characteristics